Globalization and the Challenge for Developing Countries - Yusuf, Shahid (World Bank, Washington, DC, 2014)
Rsearch on the sources of growth shows several factors to be relevant to all countries, rich or poor. Whether developing countries can substantially raise per capita incomes depends on policies that address these variables: labor, human capital, capital investment in research and development, technological progress, and the increase in total factor productivity arising from scale economies, the effects of agglomeration, externalities, and institutions that secure rights and minimize transaction costs. The author argues that a comprehensive approach to globalization, managed, and abetted by good policies, can magnify the effects of growth-promoting measures. Among his observations: 1) Returns from investment in skills are much greater in a more technologically advanced and integrated economy. 2) Trade, by enlarging markets, reinforces those gains, and the option to migrate further augments the value of skills. The growing worldwide gap in income between skilled and unskilled workers suggests how much more fruitful skills are under globalization. 3) A 50 percent increase (or even a doubling) in growth rates demands a vast amount of capital, embodying modern technology and the knowledge needed to put it to best use. The international economy can be a source of such capital. 4) Openness, combined with spatially neutral domestic policies and the scaling back of regulatory constraints on domestic business activities, can unleash the full force of agglomeration economies and networking externalities, allowing industrial clusters to emerge in metropolitan regions. 5) Openness is also the best way for low-income countries to tap into technologies that will galvanize agriculture (low-income countries' economic center) and manufacturing activities and nourish indigenous technological advance. 6) No research convincingly makes the case for delaying openness or for sequencing the various elements of openness. A good case can be made for embracing all the key elements of globalization at the same time--while sequencing (where needed) the pace of integration in such areas as trade and finance.